PENINGKATAN PENGETAHUAN SISWA SMP TENTANG DAMPAK NEGATIF GAME ONLINE BAGI KESEHATAN - Mustika Sari, Irma; Dwi Prajayanti, Eska (P3M STIKES Aisyiyah Surakarta, 2017)
The level of online game usage in Indonesia has increased. This is in line with the development of Internet technology and computer networks. In Indonesia fans of online games ranging from among children, adolescents and adults, and most are teenagers. The explosion of online games is a reflection of the rapidly growing computer network that used to be a small scale to the internet and continues to grow until now. Traditionally traditional games are beginning to move on to more modern games. Online games can have fun effects for fans and can cause addiction. Addictions to online games can have a negative impact on health. For that needed socialization or health counseling about the negative impact of the use of online games for the health of junior high school students when used in excess and disproportionate. The outward form of this devotional activity is the improvement of students' knowledge about the negative impact of online games on health.